Structure–activity relationship and crystallographic studies on 4-hydroxypyrimidine HIF prolyl hydroxylase domain inhibitors - Holt-Martyn, JP; Chowdhury, R; Tumber, A; Yeh, T-L; Abboud, MI; Lippl, K; Lohans, CT; Langley, GW; Figg Jr, W; McDonough, MA; Pugh, CW; Ratcliffe, PJ; et al. (Wiley, 2019)
The 2‐oxoglutarate‐dependent hypoxia inducible factor prolyl hydroxylases (PHDs) are targets for treatment of a variety of diseases including anaemia. One PHD inhibitor is approved for use for the treatment of renal anaemia and others are in late stage clinical trials. The number of reported templates for PHD inhibition is limited. We report structure–activity relationship and crystallographic studies on a promising class of 4‐hydroxypyrimidine‐containing PHD inhibitors.